Mild traumatic brain injury, PTSD symptom severity, and behavioral dyscontrol: a LIMBIC-CENC study - Stromberg, Kelsee M.; Martindale, Sarah L.; Walker, William C.; Ou, Zhining; Pogoda, Terri K.; Miles, Shannon R.; Dismuke-Greer, Clara E.; Carlson, Kathleen F.; Rowland, Jared A.; O’Neil, Maya E.; Pugh, Mary Jo (Frontiers in Neurology, 2024)
Background Behavioral dyscontrol occurs commonly in the general population and in United States service members and Veterans (SM/V). This condition merits special attention in SM/V, particularly in the aftermath of deployments. Military deployments frequently give rise to posttraumatic stress disorder (PTSD) and deployment-related mild TBI traumatic brain injury (TBI), potentially leading to manifestations of behavioral dyscontrol. Objective Examine associations among PTSD symptom severity, deployment-related mild traumatic brain injury, and behavioral dyscontrol among SM/V. Design Secondary cross-sectional data analysis from the Long-Term Impact of Military-Relevant Brain Injury Consortium – Chronic Effects of Neurotrauma Consortium prospective longitudinal study among SM/V (N = 1,808). Methods Univariable and multivariable linear regression models assessed the association and interaction effects between PTSD symptom severity, as assessed by the PTSD Checklist for the Diagnostic and Statistical Manual, 5th edition (PCL-5), and deployment-related mild TBI on behavioral dyscontrol, adjusting for demographics, pain, social support, resilience, and general self-efficacy. Results Among the 1,808 individuals in our sample, PTSD symptom severity (B = 0.23, 95% CI: 0.22, 0.25, p < 0.001) and deployment-related mild TBI (B = 3.27, 95% CI: 2.63, 3.90, p < 0.001) were significantly associated with behavioral dyscontrol in univariable analysis. Interaction effects were significant between PTSD symptom severity and deployment mild TBI (B = −0.03, 95% CI: −0.06, −0.01, p = 0.029) in multivariable analysis, indicating that the effect of mild TBI on behavioral dyscontrol is no longer significant among those with a PCL-5 score > 22.96. Conclusion Results indicated an association between PTSD symptom severity, deployment-related mild TBI, and behavioral dyscontrol among SM/V. Notably, the effect of deployment-related mild TBI was pronounced for individuals with lower PTSD symptom severity. Higher social support scores were associated with lower dyscontrol, emphasizing the potential for social support to be a protective factor. General self-efficacy was also associated with reduced behavioral dyscontrol.